DOMESTIC MARKET OBLIGATION (DMO) POLICY AND ITS IMPLEMENTATION STRATEGIES - RIDWAN SALEH (Puslitbang tekMIRA, 2012)
The increasing of coal consumption in various industries in Indonesia causes the increasing of coal domestic demand. On the other hand, the sharp increasing of coal production almost 16 times during 17 years is exported (75%) in majority. By using the polynomial quadratic approach, in year 2025, coal production is projected as 741 million tons (176% to National Energy Policy target as 421 million tons), coal exports as 509.3 million tons (275% to National Energy Policy target as 185 million tons) and domestic demand as 236 million tons. This is in accordance with the National Energy Policy (KEN=Kebijakan Energi Nasional) target. The presence of Government Regulation Number 34 year 2009 on the Domestic Market Obligation (DMO) is a breakthrough to solve the above problems. It is a challenge for the government as a regulatory board to implement this policy. Some strategic alternatives to implement this policy is by using the Budget Activities Plan (Rencana Kegiatan Anggaran Belanja = RKAB) instruments optimally, control system effectivity, and punish- ment applying consistency.